Changes of renal sinus fat and renal parenchymal fat during an 18-month randomized weight loss trial. Issue 4 (August 2018) - Zelicha, Hila; Schwarzfuchs, Dan; Shelef, Ilan; Gepner, Yftach; Tsaban, Gal; Tene, Lilac; Yaskolka Meir, Anat; Bilitzky, Avital; Komy, Oded; Cohen, Noa; Bril, Nitzan; Rein, Michal; et al.
Summary: Background & aims: Data regarding the role of kidney adiposity, its clinical implications, and its dynamics during weight-loss are sparse. We investigated the effect of long-term weight-loss induced intervention diets on dynamics of renal-sinus-fat, an ectopic fat depot, and %renal-parenchymal-fat, lipid accumulation within the renal parenchyma. Methods: We randomized 278 participants with abdominal obesity/dyslipidemia to low-fat or Mediterranean/low-carbohydrate diets, with or without exercise. We quantified renal-sinus-fat and %renal-parenchymal-fat by whole body magnetic-resonance-imaging. Results: Participants (age = 48 years; 89% men; body-mass-index = 31 kg/m 2 ) had 86% retention to the trial after 18 months. Both increased renal-sinus-fat and %renal-parenchymal-fat were directly associated with hypertension, and with higher abdominal deep-subcutaneous-adipose-tissue and visceral-adipose-tissue (p of trend < 0.05 for all) after adjustment for body weight. Higher renal-sinus-fat was associated with lower estimated-glomerular-filtration-rate and with higher microalbuminuria and %HbA1C beyond body weight. After 18 months of intervention, overall renal-sinus-fat (−9%; p < 0.05 vs. baseline) but not %renal-parenchymal-fat (−1.7%; p = 0.13 vs. baseline) significantly decreased, and similarly across the intervention groups. Renal-sinus-fat and %renal-parenchymal-fat changes were correlated with weight-loss per-se (p < 0.05). In a model adjusted for age, sex, and visceral-adipose-tissue changes, 18 months reduction in renal-sinus-fat associated with decreased pancreatic, hepatic and cardiac fats (p < 0.05 for all) and with decreased cholesterol/high-density lipoprotein-cholesterol (HDL-c) (β = 0.13; p = 0.05), triglycerides/HDL-c (β = 0.13; p = 0.05), insulin (β = 0.12; p = 0.05) and gamma glutamyl transpeptidase (β = 0.24; p = 0.001), but not with improved renal function parameters or blood pressure. Decreased intake of sodium was associated with a reduction in %renal-parenchymal-fat, after adjustment for 18 months weight-loss (β = 0.15; p = 0.026) and hypertension (β = 0.14; p = 0.04). Conclusions: Renal-sinus-fat and renal-parenchymal-fat are fairly related to weight-loss. Decreased renal-sinus-fat is associated with improved hepatic parameters, independent of changes in weight or hepatic fat, rather than with improved renal function or blood pressure parameters. ClinicalTrials.govIdentifier: NCT01530724 .